Integrated Multi-Omics Analysis Reveals the Effect of Maternal Gestational Diabetes on Fetal Mouse Hippocampi - Luo, Si-si; Zou, Ke-xin; Zhu, Hong; Cheng, Yi; Yan, Yi-shang; Sheng, Jian-zhong; Huang, He-feng; Ding, Guo-lian (Frontiers in Cell and Developmental Biology, 2022)
Growing evidence suggests that adverse intrauterine environments could affect the long-term health of offspring. Recent evidence indicates that gestational diabetes mellitus (GDM) is associated with neurocognitive changes in offspring. However, the mechanism remains unclear. Using a GDM mouse model, we collected hippocampi, the structure critical to cognitive processes, for electron microscopy, methylome and transcriptome analyses. Reduced representation bisulfite sequencing (RRBS) and RNA-seq in the GDM fetal hippocampi showed altered methylated modification and differentially expressed genes enriched in common pathways involved in neural synapse organization and signal transmission. We further collected fetal mice brains for metabolome analysis and found that in GDM fetal brains, the metabolites displayed significant changes, in addition to directly inducing cognitive dysfunction, some of which are important to methylation status such as betaine, fumaric acid, L-methionine, succinic acid, 5-methyltetrahydrofolic acid, and S-adenosylmethionine (SAM). These results suggest that GDM affects metabolites in fetal mice brains and further affects hippocampal DNA methylation and gene regulation involved in cognition, which is a potential mechanism for the adverse neurocognitive effects of GDM in offspring.